2022
DOI: 10.1186/s12885-021-09092-w
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of screening uptake in a colorectal cancer screening intervention among Hispanics

Abstract: Background Colorectal cancer (CRC) is the second leading cause of cancer deaths in the USA. Although a number of CRC screening tests have been established as being effective for CRC prevention and early detection, rates of CRC screening test completion in the US population remain suboptimal, especially among the uninsured, recent immigrants and Hispanics. In this study, we used a structural equation modelling approach to identify factors influencing screening test completion in a successful CRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Notably, findings of this research suggested that self-efficacy was the most powerful predictor of the six subconstructs of PMT, similar to research findings of other investigators [ 32 , 35 , 36 ]. This positive connection showed that those individuals with greater perceptions of self-efficacy tended to overcome more obstacles, and had much more confidence to participate in CRC screening [ 37 , 38 ]. Hence, it is necessary to emphasize self-efficacy when designing and carrying out various health education interventions to further improve screening uptake and mitigate the threat of CRC [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, findings of this research suggested that self-efficacy was the most powerful predictor of the six subconstructs of PMT, similar to research findings of other investigators [ 32 , 35 , 36 ]. This positive connection showed that those individuals with greater perceptions of self-efficacy tended to overcome more obstacles, and had much more confidence to participate in CRC screening [ 37 , 38 ]. Hence, it is necessary to emphasize self-efficacy when designing and carrying out various health education interventions to further improve screening uptake and mitigate the threat of CRC [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a study showed that most epidemiologic patterns of GI cancer including CRC in Chinese American immigrants were closer to those of the people of their new country of residence compared to those of their original country, indicating a shift in environmental exposures which may change cancer risk [59]. Fatalistic beliefs present in cultures of origin persist and affect adherence to screening [47,[60][61][62][63]. In addition, many cultures have a bias towards first seeking complementary and alternative medicine, where screening does not feature as prominently [47,64].…”
Section: Culture-related Barriers Among Us Immigrantsmentioning
confidence: 99%
“…Using an instrument adapted from the preventive health paradigm, Salimzadeh et al concluded that most respondents reported poor attitudes toward CRC screening [18]. Shokar et al, inspired by the Health Belief Model, found that self-efficacy, perceived advantages, and fatalism may be targeted to enhance the effectiveness of CRC screening initiatives [19]. Significantly lower degrees of response efficacy, higher perceived barriers, and poorer levels of self-efficacy were all social cognitive determinants of non-adherence to CRC screening, as mentioned by a study detecting behavioral and demographic predictors of adherence to CRC screening tests [20].…”
Section: Introductionmentioning
confidence: 99%